Acute on/off effects and chronic blood pressure reduction after long-term baroreflex activation therapy in resistant hypertension. Issue 8 (August 2015) - Halbach, Marcel; Hickethier, Tilman; Madershahian, Navid; Reuter, Hannes; Brandt, Mathias C.; Hoppe, Uta C.; Müller-Ehmsen, Jochen
Abstract : Background: Baroreflex activation therapy (BAT) by electrical stimulation of baroreceptors at the carotid sinus is a promising therapeutic approach to reduce elevated blood pressure (BP). To assess the efficacy of long-term BAT, we investigated acute BP alterations after device deactivation and reactivation (on/off effects) in patients on chronic BAT, as well as chronic BP reductions. Method: Resistant hypertension patients ( n = 17) were enrolled in an open-label, single-arm evaluation of unilateral BAT after exclusion of secondary hypertension. Initial eligibility criteria were SBP≥ 140 mmHg, despite stable medical therapy with at least three antihypertensive drugs including at least one diuretic. For on/off testing, several office cuff BP measurements were performed: at rest with activated device, 4–6 min after deactivation, and 4–6 min after reactivation. Results: Before BAT, mean office cuff BP was 179 ± 25 over 98 ± 18 mmHg. At the time of on/off testing (15.1 ± 8.7 months after initial activation and before deactivation), BP was reduced to 147 ± 29 over 84 ± 20 mmHg. On deactivation, SBP increased to 158 ± 38 mmHg ( P = 0.004) and DBP to 89 ± 23 mmHg ( P = 0.04). After reactivation, SBP decreased to 144 ± 34 mmHg ( P = 0.002 vs. deactivation) and DBP to 83 ± 23 mmHg ( P = 0.009). There was no correlation between duration of chronic BAT and systolic or diastolic acute on/off response. Conclusion: Unilateral BAT reduces BP in patients with resistant hypertension in the long term. There is a significant on/off effect on BP, supporting the efficacy of BAT. The acute on/off response to BAT does not depend on treatment duration. Thus, no evidence of tolerance over time to chronic BAT was found. Abstract : Supplemental Digital Content is available in the text